MENGEMBANGKAN SIKAP PEDULI LINGKUNGAN SISWA KELAS V MELALUI PEMBELAJARAN BERBASIS PROYEK PADA MATERI EKOSISTEM - Adianti, Auliya Fairah; Jayadinata, Asep Kurnia; Sujana, Atep (Jurnal Pena Ilmiah, 2019)
Level of elementary school is assumed as the most basic level for beginning doing everything. In a school commonly students just focus on cognitif aspect including ecosystem material. Truthfully, there is afective aspect which can be implemented in ecosystem material as one of scientific attitude in science it is care attitude toward environment through learning based on project in ecosystem material. That;s all, it is elaborated in developing care attitude toward environment to the fifth grade students through learning based on project in ecosystem material. The objective of this study is to know development of care attitude toward environment to the fifth grade students in through learning based on project in ecosystem material. This research uses approach of qualitative research with descriptive method. And the research design that the writer used is qualitative description. The subject of this research is fifth grade students in SDN Cilimbangan, Cimalaka district. Technique of sample is non probability sampling and purposive sampling. The instruments that the writer used are questionnaire of care attitude, list of checklist, and note of field. The conclusion of this research is development of care attitude toward environment to the fifth grade students in SDN Cilimbangan after project-based learning in the ecosystem material shows positive development, both of stable or progressive development.